Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1038/sj.ijo.0800766
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity action of oolong tea

Abstract: OBJECTIVE: Oolong tea is traditionally reported to have anti-obesity and hypolipidaemic effects. The present study was performed to clarify whether oolong tea prevented obesity induced in mice by the oral administration of a highfat diet for 10 weeks. DESIGN: High-fat diet-induced obese mice were treated with oolong tea for 10 weeks. The effects of various active fractions isolated from oolong tea on noradrenaline-induced lipolysis were examined with isolated fat cells and a cellfree system consisting of lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
137
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(149 citation statements)
references
References 8 publications
5
137
1
2
Order By: Relevance
“…3 Furthermore, we found that caffein was isolated from oolong tea as an accelerating substance of norepinephrine-induced lipolysis. 3 Therefore, we suggest that saponins of tea may have anti-obesity action through inhibiting pancreatic lipase activity in high-fat diettreated obesity mice. In this experiment, we found that teasaponin (a mixture of theasaponins E 1 and E 2 ) isolated from oolong tea inhibited pancreatic lipase in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Furthermore, we found that caffein was isolated from oolong tea as an accelerating substance of norepinephrine-induced lipolysis. 3 Therefore, we suggest that saponins of tea may have anti-obesity action through inhibiting pancreatic lipase activity in high-fat diettreated obesity mice. In this experiment, we found that teasaponin (a mixture of theasaponins E 1 and E 2 ) isolated from oolong tea inhibited pancreatic lipase in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…2 In the previous paper, we found that oolong tea prevented obesity induced by feeding a high-fat diet through inhibiting pancreatic lipase activity and accelerating catecholamineinduced fat mobilization. 3 We reported that epicatechin gallate and epigallocatechin gallate had no effect on pancreatic lipase activity, but that saponin fraction inhibited pancreatic lipase activity. 3 Furthermore, we found that caffein was isolated from oolong tea as an accelerating substance of norepinephrine-induced lipolysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Han et al (1999Han et al ( , 2001) have pointed out that slower absorption of dietary fat decreased the deposition of visceral fat. Shimoda et al (2006) have shown that CBE and caffeine, but not chlorogenic acid, suppress the elevation of the serum triglyceride level after oral oil administration to mice.…”
Section: Cumulationmentioning
confidence: 99%
“…Improved glucose tolerance and increased plasma insulin concentrations by tea, have been found in some studies which may be, in part, explained by the effect of tea antioxidants on insulin resistance and -cell function. EGCG has also been shown to suppress cytokine-inducedcell damage; this may also contribute to glucose lowering effect of tea (Gomes et al, 1995;Han et al, 1999;Kao et al, 2000;Sabu et al, 2002;Wu et al, 2004;Tsuneki et al, 2004;Wolfram et al, 2006;Igarashi et al, 2007;Badawoud et al, 2007;Ostad Rahimi et al, 2007;Potenza et al, 2007).…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%